2014
DOI: 10.19056/ijmdsjssmes/2014/v3i1/80661
|View full text |Cite
|
Sign up to set email alerts
|

Seminogram in Male Partners of Infertile Couples

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 11 publications
5
9
0
Order By: Relevance
“…Similar findings were observed in study conducted by Abrari et al 1 and Bodal et al 8 Semen volume less than 1.5ml was observed in 13.6% of cases. Bhaduri et al found 7.45% of cases with less than 1.5 ml 9 where as Jajoo and Kalyani reported 22% of cases with less than 2ml.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar findings were observed in study conducted by Abrari et al 1 and Bodal et al 8 Semen volume less than 1.5ml was observed in 13.6% of cases. Bhaduri et al found 7.45% of cases with less than 1.5 ml 9 where as Jajoo and Kalyani reported 22% of cases with less than 2ml.…”
Section: Discussionsupporting
confidence: 90%
“…Oligozoospermia was detected in 18.6% of cases.Similar findings were reported in studies conducted by Bodal et al 8 and Bhaduri et al Leucocytospermia reported in 10% of cases as a single parameter abnormality represents essential risk factor that should be treated to improve the quality of semen. Similar observations were reported by Lemkecher et al 13 The common multiple factor abnormality in the study population was Oligoasthenoterato zoospermia (OAT syndrome) and Oligoasthenozoospermia.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Macro and microscopic assessment of semen samples was carried out according to WHO guidelines. 13 Patients fulfilling the inclusion criteria were taken up for varicocelectomy.…”
Section: Exclusion Criteriamentioning
confidence: 99%